Unexpectedly high dimethyl sulfide concentration in high-latitude Arctic sea ice melt ponds. Issue 10 (29th August 2019) - Park, Keyhong; Kim, Intae; Choi, Jung-Ok; Lee, Youngju; Jung, Jinyoung; Ha, Sun-Yong; Kim, Joo-Hong; Zhang, Miming
Abstract : Dimethyl sulfide (DMS) production in the northern Arctic Ocean has been considered to be minimal because of high sea ice concentration and extremely low productivity. Abstract : Dimethyl sulfide (DMS) production in the northern Arctic Ocean has been considered to be minimal because of high sea ice concentration and extremely low productivity. However, we found DMS concentration (1–33 nM) in melt ponds on sea ice at a very high latitude (78°N) in the central Arctic Ocean to be up to ten times that in the adjacent open ocean (<3 nM). We divided melt ponds into three categories: freshwater melt ponds, brackish melt ponds, and open saline melt ponds. Melt ponds from each category had different formation mechanisms and associated DMS contents. Closed brackish ponds (salinity of >20) had particularly high DMS concentration. Water in brackish ponds was mixed with open ocean water in the past via a hole at the bottom of the floe that kept the pond open to the ocean; therefore, unlike freshwater melt ponds, brackish ponds became sites of DMS accumulation. Our results suggest that continuous increase in melt pond coverage on Arctic sea ice could considerably impact future Arctic climate as well as enhancing DMS concentration in the Arctic atmosphere.